A Comparison Between GaAs Mesfet and Si NMOS ESD Behaviour - A. J. Franklin; E. A. Amerasekera; D. S. Campbell (Active and Passive Electronic Components)
Work is in hand at Loughborough University to investigate and compare the ESD sensitivity of GaAs D-MESFETs and unprotected enhancement mode NMOS structures.